1991
DOI: 10.1063/1.349070
|View full text |Cite
|
Sign up to set email alerts
|

Trapping of atomic hydrogen in silicon by disordered regions

Abstract: This paper addresses issues related to migration and acceptor neutralization of hydrogen (H) in crystalline Si. From spreading resistance measurements, it is shown that disordered regions, both surface and subsurface, directly inhibit the penetration of H. Further, these effects are shown to be independent of the kind of disorder and the method of hydrogenation. Secondary-ion mass spectrometry profiles of deuterated samples confirm the suppression of deuterium movement through the disordered regions. We observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…[12][13][14] Depending on the treatment conditions, posthydrogenation annealing at temperatures higher than 400°C may lead to the transformation of vacancy-type defects into large platelets due to the presence of hydrogen. This results in the growth of bigger cavities at the expense of smaller ones.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Depending on the treatment conditions, posthydrogenation annealing at temperatures higher than 400°C may lead to the transformation of vacancy-type defects into large platelets due to the presence of hydrogen. This results in the growth of bigger cavities at the expense of smaller ones.…”
Section: Discussionmentioning
confidence: 99%
“…By post-hydrogenation they could recover the initial properties. Srikanth and Ashok [13] have reported hydrogenation of polycrystalline and amorphous silicon and they found that post-hydrogenation through the disordered region has very low penetration depth. They tried two different hydrogenation processes, implantation and electron cyclotron resonance (ECR) plasma, and found the same results.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Therefore, during subsequent annealing hydrogen could be captured in other defects (i.e. vacancy-type defects for He implantation), and retard the annealing-out of the defects if these defects are present in the same sample [20]. Moreover, in-diffusion of hydrogen into the developing cavities could also generate additional internal pressure within the cavities.…”
Section: A) B)mentioning
confidence: 99%